Time-Dependent Pathological Changes in Hypoperfusion-Induced Abdominal Aortic Aneurysm - Kugo, Hirona (Biology (Basel), 2021)
SIMPLE SUMMARY: Abdominal aortic aneurysm (AAA) is a vascular disease that involves gradual dilation of the abdominal aorta and has a high mortality due to rupture. Hypoperfusion due to the obstruction of vasa vasorum, which is a blood supply system in the aortic wall, may be an important factor involved in AAA pathophysiology. A time-dependent analysis is important to understand the pathological cascade following hypoperfusion in the aortic wall. In our study, time-dependent analysis using a hypoperfusion-induced animal model showed that the dynamics of many AAA-related factors might be associated with the increased hypoxia-inducible factor-1α level. Hypoperfusion due to stenosis of the vasa vasorum might be a new drug target for AAA therapeutics. ABSTRACT: Hypoperfusion due to vasa vasorum stenosis can cause wall hypoxia and abdominal aortic aneurysm (AAA) development. Even though hypoperfusion is an important contributor toward pathological changes in AAA, the correlation between hypoperfusion and AAA is not fully understood. In this study, a time-dependent semi-quantitative pathological analysis of hypoperfusion-induced aortic wall changes was performed to understand the mechanisms underlying the gradual degradation of the aortic wall leading to AAA formation. AAA-related factors evaluated in this study were grouped according to the timing of dynamic change, and five groups were formed as follows: first group: angiotensin II type 1 receptor, endothelin-1 (ET-1), and malondialdehyde (MDA); second group: matrix metalloproteinase (MMP)-2, -9, -12, M1 macrophages (Mac387+ cells), and monocyte chemotactic protein-1; third group: synthetic smooth muscle cells (SMCs); fourth group: neutrophil elastase, contractile SMCs, and angiotensinogen; and the fifth group: M2 macrophages (CD163+ cells). Hypoxia-inducible factor-1α, ET-1, MDA, and MMP-9 were colocalized with alpha-smooth muscle actin cells in 3 h, suggesting that hypoperfusion-induced hypoxia directly affects the activities of contractile SMCs in the initial stage of AAA. Time-dependent pathological analysis clarified the cascade of AAA-related factors. These findings provide clues for understanding complicated multistage pathologies in AAA.